Two-Step Generation of Oligodendrocyte Progenitor Cells From Mouse Fibroblasts for Spinal Cord Injury - Lee, Yukyeong; Kim, C-Yoon; Lee, Hye Jeong; Kim, Jae Gon; Han, Dong Wook; Ko, Kisung; Walter, James; Chung, Hyung-Min; Schöler, Hans R.; Bae, Young Min; Ko, Kinarm (Frontiers in Cellular Neuroscience, 2018)
Oligodendrocyte progenitor cells (OPCs) are attracting attention as the ideal cell therapy for spinal cord injury (SCI). Recently, advanced programming techniques have made it possible to generate patient-specific cells for treating SCI. In the present study, we used directly-induced neural stem cells from fibroblasts to establish OPCs (DN-OPCs) capable of proliferation, and confirmed their OPC-specific characteristics. Also, we evaluated the effect of transplanted DN-OPCs on SCI in rats. The DN-OPCs exhibited an OPC-specific phenotype and electrophysiological function, and could be differentiated into oligodendrocytes. In the SCI model, transplanted DN-OPCs improved behavior recovery, and showed engraftment into the host spinal cord with expression of myelin basic protein. These results suggest that DN-OPCs could be a new source of potentially useful cells for treating SCI.